1999
DOI: 10.1001/archinte.159.19.2312
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of an Enhanced Patient Compliance Program for Helicobacter pylori Therapy

Abstract: Objectives:To determine whether an enhanced compliance program (ECP) improves patient compliance with bismuth subsalicylate, metronidazole, and tetracycline hydrochloride (BMT) triple therapy for the treatment of Helicobacter pylori infection and to identify factors that affect compliance with therapy.Design: A randomized controlled trial conducted in 4 staff-model health centers of a health maintenance organization in Massachusetts. Patients and Methods:A total of 125 patients 18 years of age or older with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 21 publications
4
90
1
2
Order By: Relevance
“…This phenomenon is called as 'white-coat adherence' [14,15] and a randomized controlled trial demonstrated that the techniques such as a received medication counseling (written and oral) from a pharmacist, as well as a telephone call follow-up after the initiation of the therapy, increased the number of patients who took more than 90% of the medications; we performed both the pharmacist counseling and the telephone call follow-up for evaluating the patients' compliance. This could be the major source of the motivation for the greater compliance rate of our study [16]. In the randomized study, to evaluate the efficacy of the H. pylori eradication regimes, 90% of the patients used 100% of the prescribed medications correctly, and it seemed that the results of this study were similar to those of our study [17].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This phenomenon is called as 'white-coat adherence' [14,15] and a randomized controlled trial demonstrated that the techniques such as a received medication counseling (written and oral) from a pharmacist, as well as a telephone call follow-up after the initiation of the therapy, increased the number of patients who took more than 90% of the medications; we performed both the pharmacist counseling and the telephone call follow-up for evaluating the patients' compliance. This could be the major source of the motivation for the greater compliance rate of our study [16]. In the randomized study, to evaluate the efficacy of the H. pylori eradication regimes, 90% of the patients used 100% of the prescribed medications correctly, and it seemed that the results of this study were similar to those of our study [17].…”
Section: Discussionsupporting
confidence: 62%
“…In Lee et al's study, 36% of the patients had experienced a gastrointestinal intolerance, which included nausea, vomiting, diarrhoea, stomach cramps, and constipation; taste disturbance was the more frequent GI ADR, as in our study [16]. This bothering effect of metronidazole can be explained as the reason for the noncompliance to the regimens.…”
Section: Discussionsupporting
confidence: 54%
“…Lee and colleagues conducted a randomized controlled trial (RCT) to determine whether compliance differed between standard care and a program of enhanced compliance care (Lee et al 1999). They found that although the intervention and control group did not differ, adherence varied by the frequency of dosing and the total number of pills.…”
Section: Other Disordersmentioning
confidence: 99%
“…It has been shown that approximately10% of patients fail to take more than 60 % 78 The most commonly cited reason for medication noncompliance is gastrointestinal intolerance. This has implications with regards to H. pylori eradication rates.…”
Section: Compliance and H Pylori Eradicationmentioning
confidence: 99%